ESTETIKA SIMBOLIK PERANG KEMBANG WAYANG KULIT SEBAGAI MEDIA PENDIDIKAN PENGENDALIAN DIRI DALAM BUDAYA JAWA - Sigid Ariyanto; Widodo Widodo; Agus Cahyono (Universitas Negeri Makassar, 2025)
Perang Kembang is one of the important scenes in Javanese shadow puppet (wayang kulit) performance, typically presented in Pathet Sanga, a phase marked by the intensification of dramatic conflict. This scene depicts a battle between a knight and Cakil along with a group of giants, symbolizing the inner struggle of human beings in confronting their desires. However, studies on wayang as a medium for character education generally still emphasize moral messages in a broad sense and have not sufficiently elaborated on how the value of self-control is specifically represented and internalized through the aesthetic elements of the performance, particularly the configuration of characters and the structure of movements (sabetan) in the Perang Kembang scene. Departing from this gap, this article aims to examine the symbolic aesthetics of Perang Kembang by focusing on (1) how the character of Cakil and the distinctive gendiran movements of the knight construct the meaning of controlling desire, and (2) how the mechanism of internalizing these values operates through the audience’s aesthetic experience within the context of arts education. This study employs an interpretative qualitative approach grounded in the theories of aesthetic experience, artistic symbolism, and Javanese philosophy. Data were collected through performance observation, documentation, reflection on puppetry practice, and literature review. The findings indicate that the visual, vocal, and movement characteristics of Cakil, which are aggressive, represent uncontrolled desire, while the gendiran movements of the knight demonstrate qualities of control, precision, and rhythm as symbols of refined inner power. The pattern of Cakil’s death by his own dagger reinforces the ethical message that desires left unchecked have the potential to destroy their subject. These findings strengthen the contribution of this research by concretely demonstrating the relationship between movement structure, dramatic symbols, and value internalization. Thus, Perang Kembang can be positioned as a model for self-control education based on aesthetic experience, which is relevant for the development of arts education rooted in local wisdom.